A new model for the study of neuropathic pain after brachial plexus injury. Issue 2 (February 2017) - Liu, Yuzhou; Wang, Le; Meng, Chong; Zhou, Yingjie; Lao, Jie; Zhao, Xin
Abstract: The study was to introduce a new and reliable behavioral model of upper trunk of brachial plexus avulsion for the study of persistent neuropathic pain. 60 rats were divided into three groups randomly: upper trunk of brachial plexus avulsion (UTBPA) group (20), global brachial plexus avulsion (GBPA) group (20), and sham- operated group (20). The animals were tested for behavioral responsiveness before surgeries and 3, 7, 14, 21, 28, 56, 84 days after surgeries. The injured level of spinal cord was resected and the sections were processed for GFAP (astrocyte) and Iba1 (microglia) immunohistochemistry 3 weeks after surgeries. The UTBPA group developed significant signs both of mechanical and cold hypersensitivity, which matched the immunohistochemistry result, as well as the nature of avulsion was close to the clinical type of injury, the UTBPA group could be used as a suitable and effective persistent neuropathic pain model following brachial plexus injury.